Case report: Two cases of multiple evanescent white dot syndrome with transient night blindness - Miyake, Kanna; Egawa, Mariko; Mitamura, Yoshinori; Yanai, Ryoji (Frontiers in Ophthalmology, 2025)
IntroductionThis study aimed to report two cases of multiple evanescent white dot syndrome (MEWDS) with transient night blindness.Case PresentationCase 1: A 24-year-old man presented with acute visual loss and night blindness in his right eye. Examination revealed an enlarged blind spot and multiple white dots extending from the posterior pole to the peripheral retina in the right eye. Optical coherence tomography (OCT) revealed multiple disruptions of the ellipsoid zone (EZ). Full-field electroretinography (ffERG) demonstrated a more pronounced reduction in rod amplitude compared with cone amplitude in both eyes. After 3 months, the white dots, EZ disruption, and night blindness resolved spontaneously, and the ffERG amplitude normalized in the right eye. However, the enlarged blind spot persisted. Case 2: A 66-year-old woman presented with acute visual deterioration and night blindness in her right eye. The right eye exhibited an enlarged blind spot and numerous white spots widely extending from the posterior pole to the periphery. OCT revealed widespread EZ loss, and ffERG showed reduced rod and cone responses. SubTenon’s triamcinolone acetonide injection was administered, and 3 months after the injection, the night blindness, ffERG abnormalities, and EZ loss had resolved, but the enlarged blind spot remained.ConclusionMEWDS rarely causes transient night blindness due to extensive rod dysfunction. However, outer retinal layer damage is reversible, with night blindness typically resolving within a few months.